Measuring a university's environmental performance : a standardized proposal for carbon footprint assessment (2022)
The global contribution of all kinds of organizations to greenhouse gas (GHG) emissions is noteworthy. Calculating, reporting, reducing, and compensating for carbon footprints are the appropriate steps to take to guide companies toward a path that is compatible with their country's objectives for the fulfillment of the Paris Agreement. In Latin American countries, carbon footprint reporting is limited and incipient. This paper aims to start closing this gap by assessing the carbon footprint of a university operating in the city of Bogotá, Colombia. Based on a city input-output table (IOT) nested in a multiregional input-output (MRIO) table framework, we estimate the three categories of the carbon footprint (scopes 1, 2, and 3) identified by the Greenhouse Gas Protocol using an improved multiregional tiered hybrid analysis of the university's energy and other input expenditures. Our results show that 94% of the entire institution's footprint is attributed to scope 3, which represents indirect emissions linked to the upstream value chain. The results allow us to identify emission hotspots and their impact on the supply chain, which can be helpful for reducing costs and encouraging organizations, users, and suppliers to make more sustainable decisions.